Cadmium and Lead Exposure and Risk of Cataract Surgery in U.S. Adults - Wang, Weiye (Int J Hyg Environ Health, 2016)
Cataract is a major cause of visual dysfunction and the leading cause of blindness. Elevated levels of cadmium and lead have been found in the lenses of cataract patients, suggesting these metals may play a role in cataract risk. This study aimed to examine the associations of blood lead, blood cadmium and urinary cadmium with cataract risk. We identified 9,763 individuals aged 50 years and older with blood lead and cadmium levels, and a randomly selected subgroup of 3,175 individuals with available urinary cadmium levels, from the National Health and Nutrition Examination Surveys (NHANES) from 1999 to 2008 (mean age=63 years). Participants were considered to have cataract if they self-reported prior cataract surgery in NHANES’s vision examination. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed using survey logistic regression models. We identified 1737 cataract surgery cases (the weighted prevalence=14.1%). With adjustment for age, race/ethnicity, gender, education, diabetes mellitus, body mass index, cigarette smoking (serum cotinine and pack-years) and urine hydration, every 2-fold increase in urinary cadmium was associated with a 23% higher risk of cataract surgery (OR=1.23, 95% CI: 1.04, 1.46, p =0.021). We found no associations of cataract surgery with blood cadmium (OR=0.97, 95% CI: 0.89, 1.07) and blood lead (OR=0.97, 95% CI: 0.88, 1.06). Mediation analysis showed that for the smoking-cadmium-cataract pathway, the ratio of smoking’s indirect effect to the total effect through cadmium was more than 50%. These results suggest that cumulative cadmium exposure may be an important under-recognized risk factor for cataract. However, these findings should be interpreted with a caution because of inconsistent results between urinary cadmium and blood cadmium.